Analysis of Snake Bite Victims in a Tertiary Care Center - Rao, V Dharma; Bickram, P; Ramyatha, R P; Sumalatha, N (Health Renaissance, 2015)
Background: Snake-bite is a common cause of morbidity and mortality in tropical countries. In India, there are 216 species of snakes, of which only four (cobra, krait, Russell’s viper and saw scaled viper) are venomous. Objective: The aim of the study was to evaluate the epidemiological profile, clinical features, complications and mortality rate of snake bite victims admitted in a tertiary care hospital in Andhra Pradesh, India. Methods: The study was conducted at Mamata General Hospital, khammam from June 2010 to May 2012. A total of 39 cases with history of snake bite were analysed. Results: Out of 39 cases, majority of the cases were observed in the age group 20-50 year (66%). High incidence of snake bite was observed in males 62%). The common victims were farmers and housewives. The bite was commonly encountered while walking bare foot (30%) followed by while sleeping (14%). Fifty Four percent of victim were bitten during outdoor and agriculture related activities. Maximum number of cases (54%) presented within 12 hour of snake bite and 66% cases had 1-5 days of hospital stay. Majority (82%) were bitten on the legs below knee. Localized oedema at the site of bite was present in 70% victim. Fang/teeth marks were noted in (41%) cases. There were 59% neurotoxic snake bites, 26% haemolytic, 5% mixed and 8% non-poisonous snake bites. Most of the cases developed cellulitis at the site of snake bite (21%), shock (12%), and acute kidney injury (8%). One tenth of the cases required assisted ventilation and overall mortality rate was 8%. Conclusion: Snakebites are still common in the rural population of India. There is need to educate the public about the preventive measures of snake bite, advantages of early hospital referral and treatment. DOI: http://dx.doi.org/10.3126/hren.v12i1.11981 Health Renaissance 2014;12(1):24-28